2017
DOI: 10.1371/journal.pone.0173608
|View full text |Cite
|
Sign up to set email alerts
|

The relationships within the Chaitophorinae and Drepanosiphinae (Hemiptera, Aphididae) inferred from molecular-based phylogeny and comprehensive morphological data

Abstract: The Chaitophorinae is a bionomically diverse Holarctic subfamily of Aphididae. The current classification includes two tribes: the Chaitophorini associated with deciduous trees and shrubs, and Siphini that feed on monocotyledonous plants. We present the first phylogenetic hypothesis for the subfamily, based on molecular and morphological datasets. Molecular analyses were based on the mitochondrial gene cytochrome oxidase subunit I (COI) and the nuclear gene elongation factor-1α (EF-1α). Phylogenetic inferences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 69 publications
4
15
0
Order By: Relevance
“…A molecular phylogeny of Aphididae based on limited gene sequences also indicated that Drepanosiphinae and Chaitophorinae may be sister groups ( von Dohlen and Moran 2000 ; Ortiz-Rivas et al 2004 ; Ortiz-Rivas and Martínez-Torres 2010 ) and could even be combined in a single unit ( von Dohlen 2009 ). Wieczorek et al (2017) further discussed the relationship between these 2 subfamilies inferred from a molecular-based phylogeny and comprehensive morphological data and supported the separation of Chaitophorinae from Drepanosiphinae. Unfortunately, Wieczorek et al (2017) only sampled these 2 species groups and did not combine molecular and morphological data to discuss their relationships in the evolutionary framework of Aphididae.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A molecular phylogeny of Aphididae based on limited gene sequences also indicated that Drepanosiphinae and Chaitophorinae may be sister groups ( von Dohlen and Moran 2000 ; Ortiz-Rivas et al 2004 ; Ortiz-Rivas and Martínez-Torres 2010 ) and could even be combined in a single unit ( von Dohlen 2009 ). Wieczorek et al (2017) further discussed the relationship between these 2 subfamilies inferred from a molecular-based phylogeny and comprehensive morphological data and supported the separation of Chaitophorinae from Drepanosiphinae. Unfortunately, Wieczorek et al (2017) only sampled these 2 species groups and did not combine molecular and morphological data to discuss their relationships in the evolutionary framework of Aphididae.…”
Section: Discussionmentioning
confidence: 64%
“… Wieczorek et al (2017) further discussed the relationship between these 2 subfamilies inferred from a molecular-based phylogeny and comprehensive morphological data and supported the separation of Chaitophorinae from Drepanosiphinae. Unfortunately, Wieczorek et al (2017) only sampled these 2 species groups and did not combine molecular and morphological data to discuss their relationships in the evolutionary framework of Aphididae. However, the non-sister groups Chaitophorinae and Drepanosiphinae were also revealed by other molecular phylogenetic inferences ( Nováková et al 2013 ), even based on mitochondrial genome sequences ( Chen et al 2017 ).…”
Section: Discussionmentioning
confidence: 64%
“…6 and 7) and morphological analyses (Fig. 5) is not uncommon issue (Wieczorek et al, 2017; Tang et al, 2018) as both data source often suggest conflicting results. We carefully evaluated a possibility of either splitting Sirthenea into several genera, or including the other genera into our studied genus.…”
Section: Discussionmentioning
confidence: 99%
“…The subfamily Chaitophorinae (Homoptera: Aphididae) divided into two tribes Chaitophorini and Siphini, comprises about 170 species within 12 genera (Wieczorek et al, 2017); the distribution range of this subfamily is mainly in the Palaearctic (about 80% of species), and Nearctic region (Wieczorek, 2010;Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%